Orbital Decay in M82 X-2 - Bachetti Matteo; Heida Marianne; Maccarone Thomas; Huppenkothen Daniela; Israel Gian Luca; Barret Didier; Brightman Murray; Brumback McKinley; Earnshaw Hannah P; Forster Karl; Fürst Felix; Grefenstette Brian W; et al. (IOP Publishing Ltd, 2025)
M82 X-2 is the first pulsating ultraluminous X-ray source discovered. The luminosity of these extreme pulsars, if isotropic, implies an extreme mass transfer rate. An alternative is to assume a much lower mass transfer rate, but with an apparent luminosity boosted by geometrical beaming. Only an independent measurement of the mass transfer rate can help discriminate between these two scenarios. In this paper, we follow the orbit of the neutron star for 7 yr, measure the decay of the orbit ((P) over dot(orb)/(P) over dot(orb) approximate to -8.10(-6) yr(-1)), and argue that this orbital decay is driven by extreme mass transfer of more than 150 times the mass transfer limit set by the Eddington luminosity. If this is true, the mass available to the accretor is more than enough to justify its luminosity, with no need for beaming. This also strongly favors models where the accretor is a highly magnetized neutron star.